The effects of H2O on a vanadium-based catalyst for NH3-SCR at low temperatures: a quantitative study of the reaction pathway and active sites. Issue 20 (28th August 2019) - Liu, Kuo; Yan, Zidi; He, Hong; Feng, Qingcai; Shan, Wenpo
Abstract : The effects of H2 O on the adsorption amounts of NO, NO2, and NH3, NH3 -SCR reaction pathway and active site distribution over V2 O5 /WO3 –TiO2 at low temperatures were quantitatively studied by the TRM and TPSR. Abstract : The influences of H2 O on the adsorption amounts of NO, NO2, and NH3 on V2 O5 /WO3 –TiO2 and the reaction pathway at low temperatures for selective catalytic reduction of nitrogen oxides by NH3 (NH3 -SCR) were quantitatively obtained using the temperature programmed surface reaction as well as the transient response method (TRM). The active site distribution on V2 O5 /WO3 –TiO2 was also clarified quantitatively. NO x adsorption took place on [V 4+ ]–OH + [V 5+ ]–O, [V 5+ ]–OH, and [Ti 4+ ]2 –O, the surface concentrations of which were 24, 28 and 26 μmol g −1, respectively, whereas NH3 was activated on [V 4+ ]–OH + [V 5+ ]–O, [V 5+ ]–OH, [Ti 4+ ]2 –O and W species, with concentrations of 24, 28, 26 and 274 μmol g −1, respectively. The V and W species did not distribute as a monolayer. The "nitrite path", referring to the reaction between adsorbed NH3 and nitrite species to produce N2 and water (H2 O), contributed to standard and fast SCR mechanisms, but the "NH4 NO3 path", referring to the reaction between the NO gas and NH4 NO3 formed from the surface nitrates and adsorbed NH3 species to emit NO2, H2 O and N2, did not occur at low temperatures without H2 O. Both the "NH4 NO3 path" and the "nitrite path" contributed to NH3 -SCR with H2 O in the gas feed. The presence of H2 O increased the amounts of the adsorbed nitrates and ammonia at 150 °C, but hindered the reaction between the adsorbed NH3 and NO gas, lowering the SCR activity.